800 words. Season three, part one [videorecording (DVD)]. - Thomson, Erik, 1967-; Vidler, Melina, 1993-; Anthony, Benson Jack, 1997- (Acorn Media, 2018)
After relocating from the whirlwind of Sydney, newspaper columnist George Turner is slowly learning what it means to be a local in the quirky New Zealand town of Weld. He wanted his kids, Shay and Arlo, to have a fresh start after the death of his wife, but not all went according to plan. Now George must reunite his family by bringing Shay home from her self-appointed exile in Australia.